Immunosenescence and multiple sclerosis: inflammaging for prognosis and therapeutic consideration - Thakolwiboon, Smathorn; Mills, Elizabeth A.; Yang, Jennifer; Doty, Jonathan; Belkin, Martin I.; Cho, Thomas; Schultz, Charles; Mao-Draayer, Yang (Frontiers in Aging, 2023)
Aging is associated with a progressive decline of innate and adaptive immune responses, called immunosenescence. This phenomenon links to different multiple sclerosis (MS) disease courses among different age groups. While clinical relapse and active demyelination are mainly related to the altered adaptive immunity, including invasion of T- and B-lymphocytes, impairment of innate immune cell (e.g., microglia, astrocyte) function is the main contributor to disability progression and neurodegeneration. Most patients with MS manifest the relapsing-remitting phenotype at a younger age, while progressive phenotypes are mainly seen in older patients. Current disease-modifying therapies (DMTs) primarily targeting adaptive immunity are less efficacious in older patients, suggesting that immunosenescence plays a role in treatment response. This review summarizes the recent immune mechanistic studies regarding immunosenescence in patients with MS and discusses the clinical implications of these findings.